Церковний правовий порядок як складова загальносоціального правового порядку. - Крижановський, А. Ф.; Kryzhanovskyi, A. F.; Бальжик, І. А.; Balzhyk, I. A. (ВД "Гельветика", 2021)
У статті аналізується церковний правовий порядок як складова частина загальносоціального правового порядку. Визначено, що унікальна природа церковного права й церковного правового порядку є основою для нового прочитання проблеми співвідносності духовного та юридичного начал життя суспільства. Церковний правовий порядок, як і загальносоціальний, сполучається з духовністю в тому, що до сфери духовного належать усі інтелектуальні й моральні сили людини, її прагнення до свободи й порядку. Функціонування церковного правового порядку є аргументом у протистоянні тим доктринальним позиціям, які виводять правовий порядок із закону й законності, та акцентує апеляцію до права як його дійсного й надійного підґрунтя. Тому поняття правового й церковного правового порядку співвідносяться як взаємопов’язані, але водночас і відмінні явища. Правове регулювання церковних правовідносин має подвійну природу. Воно здійснюється як законодавством держави, так і правовими актами церкви. Так само амбівалентний характер має суб’єктна структура церковного правового порядку. Суб’єктний склад церковного правового порядку формує його горизонтально-вертикальну структуру (носії – віряни , служителі , ієрархи – являють собою вертикальну, а релігійні громади- горизонтальну структуру). Окремий (автономний) церковний правовий порядок в Україні як у поліконфесійному суспільстві властивий кожній конфесії. Взаємовідносини, відмінності між конфесіями, взаємодія чи протиріччя між ними так чи інакше впливають на стан церковного правового порядку в суспільстві, а також на загальносоціальний правовий порядок у цілому. Діалектика церковного й загальносоціального правопорядків проявляється в тому, що церква й релігійні організації, авторитет яких у суспільстві досить високий, здатні під- кріпити зусилля держави у сфері забезпечення правопорядку властивими їм засобами й методами.

The article explores the church legal order as a component of the general social legal order. It is determined that the unique nature of church law and church legal order is the basis for a new interpretation of the problem of the relationship between the spiritual and legal principles of society. The church legal order, as well as the general social order, is combined with spirituality in that the sphere of the spiritual includes all the intellectual and moral forces of man, his desire for freedom and order. Comprehending the spiritual origins of law and legal order, the authors proceed from the fact that they are, first of all, a spiritual value. The functioning of the church legal order is an argument in opposition to those doctrinal positions that derive the legal order from the law and legality and emphasizes the appeal to the law as its real and reliable basis. Therefore, the concepts of legal order and church legal order are correlated as interconnected, but at the same time different phenomena. The legal regulation of church relations has a dual nature. It is carried out both by the legislation of the state and by legal acts of the church. The subjective structure of the church legal order is also ambivalent. The subjective composition of the church legal order forms its horizontally-vertical structure (bearers-believers, ministers, hierarchs present vertical structure, therefore, religious communities – the horizontal structure. The separate (autonomous) church legal order in Ukraine, as in a multi-confessional society, is inherent in each denomination. Relationships, differences between denominations, interaction or contradictions between them in one way or another affect the state of the church legal order in society, as well as – the general social legal order. The dialectic of ecclesiastical and general social legal order is manifested by the fact that the church and religious organisations, whose authority in society is quite high, are able to support the state`s efforts to ensure law and order by their own means and methods.

The article explores the church legal order as a component of the general social legal order. It is determined that the unique nature of church law and church legal order is the basis for a new interpretation of the problem of the relationship between the spiritual and legal principles of society. The church legal order, as well as the general social order, is combined with spirituality in that the sphere of the spiritual includes all the intellectual and moral forces of man, his desire for freedom and order. Comprehending the spiritual origins of law and legal order, the authors proceed from the fact that they are, first of all, a spiritual value. The functioning of the church legal order is an argument in opposition to those doctrinal positions that derive the legal order from the law and legality and emphasizes the appeal to the law as its real and reliable basis. Therefore, the concepts of legal order and church legal order are correlated as interconnected, but at the same time different phenomena. The legal regulation of church relations has a dual nature. It is carried out both by the legislation of the state and by legal acts of the church. The subjective structure of the church legal order is also ambivalent. The subjective composition of the church legal order forms its horizontally-vertical structure (bearers-believers, ministers, hierarchs present vertical structure, therefore, religious communities – the horizontal structure. The separate (autonomous) church legal order in Ukraine, as in a multi-confessional society, is inherent in each denomination. Relationships, differences between denominations, interaction or contradictions between them in one way or another affect the state of the church legal order in society, as well as – the general social legal order. The dialectic of ecclesiastical and general social legal order is manifested by the fact that the church and religious organisations, whose authority in society is quite high, are able to support the state`s efforts to ensure law and order by their own means and methods.
Крижановський А. Ф. Церковний правовий порядок як складова загальносоціального правового порядку / А. Ф. Крижановський, І. А. Бальжик // Наукові праці Національного університету «Одеська юридична академія». Т. 29 / голов. ред. Ю. В. Цуркан-Сайфуліна ; МОН України, НУ «ОЮА». – Одеса : Видавничий дім «Гельветика», 2021. – C. 114-122. DOI https://doi.org/10.32837/npnuola.v28i29.723
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; загальносоціальний правовий порядок; церковний правовий порядок; церква; релігійна організація; церковне право; духовність; legal order; international legal order; church legal order; church; canon law; church law; spirituality